PERANCANGAN DAN PEMBUATAN SENSOR TDS PADA PROSES PENGENDAPAN CaCO3 DALAM AIR DENGAN METODE PELUCUTAN ELEKTRON DAN MEDAN MAGNET - Martani, Maylita; Endarko, Endarko (BERKALA FISIKA, 2014)
Total Dissolved Solids (TDS) meter has successfully been fabricated based on the principle of conductivity. Control system for monitoring the TDS level in the mini plant have been performed by microcontroller ATMega16 and Personal Computer. The study was to control a precipitation process of CaC03 in the water. Values of TDS from water sample in the mini plant have been monitored and controlled in real-time. All data have been recorded by microcontroller and then, the data will be sent to personal computer via USB interface. Monitoring data will be displayed in a computer screen. The result showed that the system could be used to control level of TDS at 356 - 300 ppm. Keywords : gravity of CaC03, Conduktivity, Control